2019
DOI: 10.1371/journal.pone.0224196
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices related to TB among the general population of Ethiopia: Findings from a national cross-sectional survey

Abstract: IntroductionEthiopia is among the high-burden countries for tuberculosis (TB), TB/HIV, and drug-resistant TB. The aim of this nationwide study was to better understand TB-related knowledge, attitudes, and practices (KAPs) and generate evidence for policy and decision-making.Materials and methodsWe conducted a cross-sectional TB KAP survey in seven regions and two city administrations of Ethiopia. Eighty kebeles (wards) and 40 health centers were randomly selected for the study. Using systematic sampling, 22 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 44 publications
12
66
1
8
Order By: Relevance
“…We also conducted qualitative interviews to understand the reasons for delay. The details of the methods are described in a published paper on Knowledge Attitude and Practice about TB in Ethiopia in 2017 [39].…”
Section: Study Design and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…We also conducted qualitative interviews to understand the reasons for delay. The details of the methods are described in a published paper on Knowledge Attitude and Practice about TB in Ethiopia in 2017 [39].…”
Section: Study Design and Samplingmentioning
confidence: 99%
“…Was imported to Open Code software and analyzed using thematic content analysis technique. Direct verbatim and results from the coding and categorization were used to develop the narrative, triangulated and synthesized with the quantitative results [39,40].…”
Section: Qualitative Datamentioning
confidence: 99%
“…[25]. Studies from different settings have examined the predictors of self-reported correct knowledge about TB transmission and found that age [26] [27], gender [11] [26] [27] [28], education levels [26] [27][28] [29], household wealth [28], occupation [29], religion [11], exposure to mass media [11] [26] [30], geographical region [26] [27] [28], and perception that TB can be cured [11] were the most signi cant predictors. Understanding knowledge of TB in general and its determinants can inform policy developers and implementers of effective community based health promotion programs.…”
Section: Read Full Licensementioning
confidence: 99%
“…Based on the analysis of seven consecutive years of PTB records, the zonal cumulative annual CNR of PTB cases was 58 per 100 000 population ranging from 47 in 2019 to 69 in 2014 per 100 000 population. The CNR of PTB cases varied across districts and kebele s. This might be related to low TCD performance due to poor community awareness level, lack of TB diagnostic services, geographic locations, and poor access to transportation facilities [ 7 9 , 29 , 30 ]. The current CNRs were found to be lower compared to CNRs reported from the Amhara region (107 per 100 000 people) [ 9 ], Gurage zone (91.7 per 100 000 people) [ 10 ] and Sidama zone (76 per 100 000 people) [ 8 ], Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…The detected PTB clusters were stable over the reporting years. The clustered distribution of PTB cases indicated that there is a need to have targeted anti-TB measures including regular community awareness creation, availing TB diagnostic and treatment services, employing active TCD to prioritized areas, improving TB service quality and avoiding TB service delays [ 29 , 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%